Intracellular Fates of Cell-Penetrating Block Copolypeptide Vesicles - Sun, Victor Z. (2010)
The block copolypeptide poly(l-homoarginine)(60)-b-poly(l-leucine)(20) (R(60)L(20)) was previously found to self-assemble into versatile vesicles with controllable size and encapsulate hydrophilic cargo. These R(60)L(20) vesicles also demonstrated the ability to cross the cell membrane and transport encapsulated cargo into different cell lines. To assess the potential for using the R(60)L(20) vesicles as drug delivery vehicles further, we have investigated their endocytosis and intracellular trafficking behavior. Using drugs that inhibit different endocytosis pathways, we identified macropinocytosis to be a major process by which the R(60)L(20) vesicles enter HeLa cells. Subsequent immunostaining experiments demonstrated that the vesicles entered the early endosomes but not the lysosomes, suggesting that they recycle back to the cell surface. Overall, our studies indicate that the R(60)L(20) vesicles are able to enter cells intact with their cargos, and although some manage to escape from early endosomes, most are trapped within these intracellular compartments.